Hepatoprotective Effects of Extracts and Polysaccharides from Seaweed - N. N. Besednova; T. S. Zaporozhets; T. A. Kuznetsova; S. P. Kryzhanovskii; N. N. Kovalev; T. N. Zvyagintseva (Антибиотики и Химиотерапия)
Antioxidants of natural origin are considered as possible agents for prevention and treatment of liver diseases. Marine algae and in particular their extracts and obtained from them sulfated polysaccharides are significant sources of natural antioxidants. The recent data on the effect of the extracts and sulfated polysaccharides of seaweed on the functional activity of the liver with injuries induced by CCl4, some drugs (paracetamol, diclofenac), N-nitrosocompounds, aflatoxin are presented in the review.Particular attention is paid to the effect of sulfated polysaccharides and in particular fucoidans on the functional activity of the liver in patients with chronic viral hepatitis C. Fucoidan is highly safe and active not only as an antioxidant but also as an inhibitor of HCV replication, has antiinflammatory and immunomodulating effects. The data of the review allow to conclude that seaweed extracts and sulfated polysaccharides may be a basis for development of new generation drugs in the future for the treatment and prevention of liver diseases.